Cohort cancer incidence among pulp and paper mill workers in British Columbia - Band, Pierre R.; Le, Nhu D.; Fang, Raymond; Astrakianakis, George; Bert, Joel; Keefe, Anya; Krewski, Daniel (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'A study was conducted to investigate cancer risks in a cohort of pulp and paper workers. ' ' METHODS ': 'All male workers with at least 1 year of employment in 14 pulp and paper mills in 1950-1992 were studied. Standardized incidence ratios (SIR) were used to compare the cancer incidence of the cohort with that of the Canadian male population. Record linkage with the National Cancer Registry was performed using the generalized iterative record linkage method. ' ' RESULTS ': 'Altogether 1756 cancer cases were observed in the entire cohort. For 15 years of work or more, the entire cohort had significantly increased SIR values for pleural and prostate cancer and skin melanoma; there was also a significantly increased risk for skin melanoma among workers in the kraft process only, rectal cancer among workers in the sulfite process only, and stomach and prostate cancer and all leukemias combined among workers in both the kraft and sulfite processes. A separate analysis comparing workers in pulping and papermaking with those in the pulping process only did not reveal any difference in cancer risk and hence did not modify the results. The SIR values for skin melanoma were not significantly increased in a comparison using the British Columbia male population. Nine of 10 pleural cancers were mesotheliomas, which likely reflect past asbestos exposure. ' ' CONCLUSIONS ': 'The results suggest that long-term work in the pulp and paper industry is associated with excess risks of prostate and stomach cancers and all leukemias for work in both kraft and sulfite processes and of rectal cancer for work in the sulfite process only.
Keywords: British Columbia; cancer incidence; kraft; leukemias; prostate cancer; pulp and paper mill; rectal cancer; stomach cancer; sulfite; worker